User Analysis Mechanisms based Mobile Fitness System - Jong Won Lee; Han Kil Kim; Hoe Kyung Jung (Institute of Advanced Engineering and Science, 2016)
Modern men have health problems caused by lack of exercise than in the past. But most modern people do not know what to do exercise. Mobile systems for fitness to solve this problem have been developed. In this paper, by analyzing the user's BMI (Body Mass Index) Index and BMR (Basal Metabolic Rate) value, the data is made available. The processed data is provided to the user which proposes the right exercise and the appropriate level of exercise intensity, for exercise machines. This is different from detecting the movement, like the existing system, and a fitness value showing the calorie consumption caused. Thus the user is considered to be able to efficiently proceed to a movement based on the provided data.